Pengetahuan Petani tentang Lahan Pertanian Pangan Berkelanjutan (LP2B) di Kelurahan Kaisabu Baru Kota Baubau, Indonesia - Fayadh Mahdi Halida; La Aman Tabia (Jurnal Ilmiah Membangun Desa dan Pertanian, 2025)
Conversion of food land is so rampant in Baubau City that the Baubau City government is trying to curb it by establishing LP2B regulations. The efficacy of LP2B regulations needs to be studied, so this study is important. Farmers' commitment to not converting food crop land will be strong if farmers are aware of the LP2B regulations. In contrast to earlier research, this study focuses on farmer knowledge rather than only on methods or the assessment of LP2B regulations. Based on Baubau City Regional Regulation Number 6 of 2023 concerning the Protection of Sustainable Food Agricultural Land (LP2B), this study seeks to assess the extent of farmers' understanding of LP2B. This study was carried out in Kaisabu Baru Village, Sorawolio District, Baubau City, in February 2025. The research population consisted of 71 farmers, and all members of the population were used as research samples. The variables in this study are farmers' knowledge about LP2B. Data analysis techniques using rating scales, where farmers' knowledge was categorized as high (score range: 2.34-3.00), moderate (score range: 1.67-2.33), or low (score range: 1.00-1.66). The research results concluded that farmers' knowledge of LP2B in Kaisabu Baru Village, Baubau City, was in the low category, with an average score of 1.46%. The low level of farmers' knowledge about LP2B stems from the lack of explicit, comprehensive socialization. Practical recommendations that can be made to improve LP2B in general in Baubau City, namely, establishing technical guidelines for implementing LP2B and clearly re-mapping the location of LP2B land and the status of LP2B land ownership based on spatial data from satellite images and GIS software, because it concerns the effectiveness of providing LP2B incentives to farmers.